Dynamics of Functionality and Usability of the Use of BSI Mobile and BYOND by BSI on Public Preferences in Transactions - Silvia Maulida; Alfiyah Nururokhmah; Kharis Fadlullah Hana (IJIEF: Indonesian Journal of Islamic Economics and Finance, 2025)
In the digital age, the adoption of banking services through mobile applications is increasingly important. Although BSI Mobile and BYOND by BSI offer various features to make transactions easier, the level of use of these apps varies among customers. This study aims to analyze the influence of functionality, usability (ease of use), and user feedback on public preferences in using two mobile banking applications owned by Bank Syariah Indonesia (BSI), namely BSI Mobile and BYOND by BSI. The method used was a comparative quantitative approach, with data collection through a questionnaire involving 74 respondents who were active users of both applications. Data analysis was carried out through validity, reliability, classical assumption tests (normality, multicollinearity, heteroscedasticity), and multiple linear regression. The results showed that only the usability variable had a positive and significant influence on public preferences (p = 0.015), while functionality (p = 0.252) and user feedback (p = 0.056) had a positive but insignificant effect. These findings emphasize that ease of use is prioritized by the public over the number of features or developers' responses to user feedback. The implications of this study emphasize the importance of improving interface and user experience aspects to encourage the wider adoption of mobile banking services.